Penguatan moderasi beragama pada peserta didik melalui kurikulum Merdeka - Nurdaeni, Ni Made; Indra, Hasbi; Alim, Akhmad (TAWAZUN: Jurnal Pendidikan Islam, 2024)
Religious moderation has an important role as a mediator in easing divisions due to differences in beliefs. Indonesia, as a multicultural country with diverse beliefs, often faces misunderstandings that disrupt the life of the nation. Strengthening religious moderation from an early age in students is important to avoid radical religious thinking and foster an open attitude towards other beliefs. This study aims to examine the implementation of strengthening religious moderation in the independent curriculum with the Qur'an and Hadith approach at SDN Bengle, Bogor Regency. This study also aims to explore the role of teachers in shaping the character of religious moderation in students as well as analyzing the supporting and inhibiting factors for the implementation of this program. This research uses a descriptive qualitative approach. The research site is SDN Bengle, a driving school that implements the independent curriculum. Data were obtained through interviews and documentation, and analyzed with the stages of data collection, data reduction, data presentation, and conclusion drawing. The veracity of the data was verified through triangulation of sources and techniques. This research resulted in several important findings. First, teachers have the main role as responsible, successor, developer, implementer, and figure in building religious moderation at Bengle Elementary School. Second, the values of religious moderation that are built include fairness, balance, simplicity, and unity. Third, supporting factors include the readiness and experience of teachers in implementing religious moderation programs in accordance with the independent curriculum. However, the limited religious facilities at school become an obstacle in fostering the character of students. The implementation of strengthening religious moderation in the independent curriculum at Bengle Elementary School is in accordance with the guidance of the Qur'an and Hadith. The main role of teachers in shaping the character of religious moderation and the values contained in it has a positive impact. Although challenges in the facility still exist, proactive measures have been taken to maintain religious diversity and harmony among students. Abstrak Moderasi beragama memiliki peran penting sebagai penengah dalam meredakan perpecahan akibat perbedaan keyakinan. Indonesia, sebagai negara multikultural dengan beragam kepercayaan, sering menghadapi kesalahpahaman yang mengganggu kehidupan berbangsa dan bernegara. Penguatan moderasi beragama sejak usia dini pada peserta didik menjadi penting guna menghindari pemikiran agama yang radikal dan memupuk sikap terbuka terhadap kepercayaan lain. Penelitian ini bertujuan untuk mengkaji implementasi penguatan moderasi beragama dalam kurikulum merdeka dengan pendekatan Al-Qur'an dan Hadits di SDN Bengle, Kabupaten Bogor. Penelitian ini juga bertujuan untuk mengeksplorasi peran guru dalam membentuk karakter moderasi beragama pada siswa serta menganalisis faktor pendukung dan penghambat pelaksanaan program ini. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Tempat penelitian adalah SDN Bengle, sebuah sekolah penggerak yang menerapkan kurikulum merdeka. Data diperoleh melalui wawancara dan dokumentasi, dan dianalisis dengan tahapan pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Kebenaran data diverifikasi melalui triangulasi sumber dan teknik. Penelitian ini menghasilkan beberapa temuan penting. Pertama, guru memiliki peran utama sebagai penanggung jawab, penerus, pengembang, pelaksana, dan figur dalam membangun moderasi beragama di SDN Bengle. Kedua, nilai-nilai moderasi beragama yang dibangun meliputi adil, seimbang, kesederhanaan, dan kesatuan. Ketiga, faktor pendukung meliputi kesiapan dan pengalaman guru dalam mengimplementasikan program moderasi beragama yang sesuai dengan kurikulum merdeka. Namun, keterbatasan fasilitas keagamaan di sekolah menjadi penghambat dalam pembinaan karakter peserta didik. Implementasi penguatan moderasi beragama dalam kurikulum merdeka di SDN Bengle telah sesuai dengan panduan Al-Qur'an dan Hadits. Peran utama guru dalam membentuk karakter moderasi beragama dan nilai-nilai yang terkandung dalamnya memiliki dampak positif. Meskipun tantangan dalam fasilitas masih ada, langkah-langkah proaktif telah diambil untuk menjaga keragaman beragama dan harmoni di antara siswa.